Outcome of Microsurgical Clipping of Intracranial Aneurysms in Bir Hospital - Sharma, Gopal Raman; Kausal, Prashant; Jha, Rajiv; Khadka, Nilam; Adhikari, Dhruba Raj; Bista, Prakash; Sultania, Pawan Kumar (Nepal Journal of Neuroscience, 2011)
Available with full text